Borders, trade and welfare - Anderson, James E. 1943- (National Bureau of Economic Research <Cambridge, Mass.>: NBER working paper series, 2001)
International economic integration yields large potential welfare effects, even in a static constant returns competitive world economy. Our method is novel. The effect of border barriers on trade flows is often inferred from gravity models. But their rather atheoretic structure precludes welfare analysis. Computable general equilibrium models are designed for tight welfare analysis, but lack econometric foundation. Our method combines these approaches. Gravity models based on Anderson's (1979) interpretation are full general equilibrium models of a special simple sort. In Anderson and van Wincoop (NBER WP 8079, 2001) we develop and estimate this structure, then calculate the comparative static effects on trade flows of border barriers. In this paper we further deploy the model to explore the comparative statics of welfare with respect to borders, to currency unions and to NAFTA. Our NAFTA exercise does a much better job of replicating the actual trade flow changes than do computable general equilibrium models. An interesting implication is that terms of trade changes are very important, even for small' countries such as Mexico.